DEVELOPING DILEMMA DISCUSSION METHOD IN AKHLAQ LEARNING TO PROMOTE STUDENT’S MORAL REASONING - Ainul Yaqin (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract:Enhancing moral reasoning is the main goal of education in the perspective of cognitive-developmental theory. Strategies, approaches or learning methods are chosen based on the effectiveness in changing the level of moral reasoning of students from level of pre-conventional, to conventional and post-conventional. Dilemma Discussion Method has proven its effectiveness in increasing moral reasoning. Therefore, in order to be used in Akhlak learning (part of Pendidikan Agama Islam material) of the classroom, it is important to develop the steps of implementation (syntax) by using the principle of cognitive developmental theory. The results of this Research and Development (R & D) Design indicate that the product in the form of learning syntax from Dilemma Discussion Method is declared as valid with a mean score of 4.38 (greater than the criteria). Thus the product of development research in the form of a dilemma discussion method in learning Akhlaq is worth for being implemented.Abstrak:Peningkatan penalaran moral peserta didik merupakan tujuan utama pendidikan dalam perspektif teori cognitive-developmental. Strategi, pendekatan ataupun metode pembelajaran seharusnya dipilih berdasarkan keefektifannya dalam mengubah level penalaran moral peserta didik dari pre-conventional, menuju level conventional dan post-conventional. Metode diskusi dilema telah dibuktikan keefektifannya dalam meningkatkan penalaran moral. Oleh sebab itu, agar dapat digunakan dalam pembelajaran akhlak/moral (bagian dari mata pelajaran Pendidikan Agama Islam) di kelas, perlu diupayakan pengembangannya berupa langkah-langkah pelaksanaannya (sintak) metode tersebut dengan menggunakan prinsip-prinsip belajar cognitive developmental theory. Hasil penelitian pengembangan (Research & Development) ini menunjukkan bahwa produk berupa sintak pembelajaran dari metode diskusi dilemma dinyatakan valid karena telah memenuhi persyaratan validitas produk yakni mendapatkan skor rerata 4,38. Dengan demikian produk penelitian pengembangan berupa metode diskusi dilema dalam pembelajaran akhlaq layak untuk diimplementasikan.